Extraction and amplification of DNA from Brazilian Red propolis - Jain, Sona Arun; Marchioro, G. M.; Costa, A. C.; Araujo, E. D. (Scientia Plena, 2014)
Propolis is a resinous mixture of plant origin collected by honey bees. The chemical composition and biological activity of propolis depends on its botanical origin thus making it important to connect a particular propolis to its plant source. This manuscript describes DNA extraction from Brazillian red propolis and also shows how the extracted DNA can be utilized as a new alternative to determine the botanical origin of propolis. DNA from propolis was extracted using a CTAB-based method and the extracted DNA was proved to be of good quality for PCR amplification. DNA extraction was carried out from various samples collected independently with similar results proving the successfulness of the described protocol. The extracted DNA was amplified by PCR, using plant specific primers. Sequencing of the PCR amplified bands can be utilized for the identification of its botanical origin.